Irregularity Protection of Citizens' Constitutional Rights to the Administrative Silence: Ketidakteraturan Perlindungan Hak Konstitusional Warga Negara Atas Sikap Diam Badan dan/atau Pejabat Pemerintahan - Umar, Umar Dani (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
The Administrative's silence legally was an administrative error, however there are no standard to rule the mechanisms for protecting citizens against those an administrative error. This Research have two objectives. First of all, to analyze whether the changes of negative fictitional to positive fictitional are form of legal irregularity, secondly to study regulatory impact of Positive fictional after the issuance of Law number 11 of 2020 against on the protection of citizens' rights. This Research use normative legal research. The Result of this research showed that repeal of norm can be done by changing those law itself or because of the constitutional court decision. negation of negative fictitional validity into chapter 3 law number 5 of 1986 to the positive fictitional through chapter 53 law number 11 of 2020 impact two things. First, remove access of constitutional citizens right, second, automatic approval decision without supervision can be used as a legality tool and may harm the third parties